Nano sizing agent reinforced quartz fiber cloth composite material and preparation method thereof

Through the preparation method of quartz fiber cloth composite material reinforced by nanoslurry agent, nanohydrophobic particles are deposited on the surface of quartz fibers by aerosol deposition technology, which solves the problem of quartz fibers being easily absorbed and vacuumed, and improves the mechanical properties and hydrophobicity of the composite material.

CN119409996APending Publication Date: 2025-02-11HUBEI UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411769005.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Quartz fibers are prone to absorb water and vacuum in high heat and high humidity environments, resulting in structural damage and degradation of performance. It is difficult for conventional organic sizing agents to effectively fill the nanopores and micropores, reducing the structure and performance of composite materials.

Method used

The preparation method of the composite material of reinforced quartz fiber cloth is prepared by shear dispersion method, and the nano-sizing emulsion is deposited on the surface of the quartz fiber cloth under the protection of argon by aerosol deposition technology to form nano-hydrophobic particles , improve the hydrophobicity of the fiber surface and the bonding strength with the resin.

Benefits of technology

The hydrophobic modification of the surface of quartz fiber is realized, the interface bonding between fiber and resin is improved, and the mechanical properties of composite materials are enhanced, and it is suitable for the spinning field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169762050000081
    Figure BDA0005169762050000081
Patent Text Reader

Abstract

The invention provides a nano sizing agent reinforced quartz fiber cloth composite material and a preparation method thereof, and belongs to the technical field of composite materials. The preparation method comprises the following steps: shearing and dispersing a surfactant, a solvent and nano hydrophobic particles to obtain a nano sizing emulsion; depositing the nano sizing emulsion on the surface of the quartz fiber cloth by using an aerosol deposition method; and finally, carrying out hot press molding on the modified quartz fiber cloth and a resin matrix to obtain the composite material. The hydrophobic property of the modified quartz fiber cloth obtained by the method is improved, and the contact angle between the modified quartz fiber cloth and water drops can reach 161.5 degrees; according to the composite material obtained by modifying the quartz fiber cloth, the interface bonding force of resin and fibers is strong, the mechanical property of the composite material is remarkably improved, and a tensile strength test shows that the flexibility of the composite material is also remarkably improved, and the composite material is not easy to break during stretching and has good mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a nano-sizing agent reinforced quartz fiber cloth composite material and a preparation method thereof. Background Art

[0002] Quartz fiber is an inorganic glass fiber drawn from high-purity silicon dioxide, with a diameter of several microns to tens of microns. Quartz fiber not only maintains the heat resistance, insulation, ablation resistance, thermal shock resistance and chemical stability of quartz itself, but also has soft and woven properties, and is widely used in many heat-resistant protective equipment.

[0003] During the drawing process, quartz fiber is prone to defects such as micropores and cracks due to complex components, process fluctuations and thermal stress. In order to maintain the bundling of quartz fiber for easy weaving, a wetting agent must be added during the fiber production process. However, quartz fiber equipment is stored in a high-heat and high-humidity environment, and the wetting agent is easy to volatilize. Since the defective surface is rich in hydroxyl groups, it is very easy to absorb moisture and dust, destroy the structure, and affect the performance of the equipment. In order to overcome the problem that quartz fiber products are easy to absorb moisture and dust, people usually use sizing agents to treat the surface of quartz fibers. However, when using organic sizing agents for conventional coating, it is difficult to efficiently fill nanopores and micropores rich in active hydroxyl groups, which can easily reduce the structure and performance of organic composite materials.

[0004] Therefore, how to obtain a nano-sizing agent reinforced quartz fiber cloth composite material, which can not only make the quartz fiber surface hydrophobic and smooth, which is conducive to spinning, but also ensure that the quartz fiber and the resin are firmly combined to improve the mechanical properties of the composite material, is a technical problem that needs to be solved at present. Summary of the invention

[0005] The object of the present invention is to provide a nano-sizing agent reinforced quartz fiber cloth composite material and a preparation method thereof, so as to solve the technical problem that the quartz fiber micropores are easy to absorb water and dust, and the interface bonding with the resin is poor.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a nano-sizing agent reinforced quartz fiber cloth composite material, comprising the following steps:

[0008] (1) dispersing a surfactant, a solvent and nano-hydrophobic particles by shearing to obtain a nano-sizing emulsion;

[0009] (2) under argon protection, the nano-sizing emulsion is deposited on the surface of the quartz fiber cloth by an aerosol deposition method, and the modified quartz fiber cloth is obtained after drying;

[0010] (3) mixing resin powder and inorganic powder to obtain mixed powder;

[0011] (4) Using the mixed powder as the resin matrix and the modified quartz fiber cloth as the reinforcement, a nano-sizing agent reinforced quartz fiber cloth composite material is obtained by hot pressing.

[0012] Furthermore, the aerosol deposition method is specifically:

[0013] The nano-sizing emulsion is subjected to spark ablation to obtain nano-aerosol, and the nano-aerosol is deposited on the surface of the quartz fiber cloth by carrier gas;

[0014] The flow rate of the carrier gas is 100-300 m / s.

[0015] Furthermore, the surfactant comprises one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, polyoxyethylene alkylamine and polyoxyethylene alkylamide; the solvent comprises one or more of N-methylpyrrolidone, methanol, ethanol, acetone, dioxane and tetrahydrofuran.

[0016] Furthermore, the nano-hydrophobic particles include one or more of polyethylene nano-particles, sodium poly(ethylene acid) nano-particles, zinc oxide hydrophobic nano-particles, aluminum oxide hydrophobic nano-particles, super-hydrophobic PDMS nano-particles and nano-silicon dioxide, and the particle size of the nano-hydrophobic particles is 100-200 nm.

[0017] Furthermore, the mass ratio of the surfactant, the solvent and the nano-hydrophobic particles is 20-30:20-30:15-35.

[0018] Furthermore, the resin powder comprises one or more of phenolic resin, cyanate resin and polyimide resin; the inorganic powder comprises one or more of talcum powder, calcium carbonate powder and wollastonite powder; and the mass ratio of the resin powder to the inorganic powder is 1:1-3.

[0019] Furthermore, the mass ratio of the reinforcement to the resin matrix is ​​1:1 to 1.5.

[0020] Furthermore, the temperature of the hot pressing molding is 300-400° C., and the pressure is 1-10 MPa.

[0021] The invention also provides a nano-sizing agent reinforced quartz fiber cloth composite material.

[0022] Beneficial effects of the present invention:

[0023] The nanophase introduced into the sizing agent of the present invention is conducive to improving the roughness of the fiber surface, producing a good physical meshing effect at the interface between the fiber and the resin, and further enhancing the interface bonding strength. The present invention uses aerosol deposition technology to form an aerosol by spark ablation of the sizing agent, and then uses a carrier gas to realize surface deposition of the aerosol particles under the mechanism of filtration, so that the aerosol particles are uniformly deposited on the surface and micropores of the quartz fiber, and the surface modification of the quartz fiber is realized. And the particle size of the aerosol particles obtained by the aerosol deposition technology of the present invention is between 0.1 and 10nm, and the diameter of the cracks on the surface of the quartz fiber is between 1 and 10μm, and the pore size of the surface micropores is between 10 and 20nm. When the surface of the quartz fiber is deposited, the aerosol particles can be effectively filled into the micropores on the surface of the quartz fiber by controlling the deposition amount, and under the mechanism of filtration, the aerosol particles will be more uniformly deposited, and the surface of the modified quartz fiber finally obtained is smoother, and the mechanical properties are also improved, which can be better applied to the spinning field.

[0024] The aerosol deposition method of the present invention can gently achieve soft landing of nano hydrophobic particles under normal pressure conditions, avoiding damage to the fiber surface caused by thermal shock, while ensuring the dispersion of the nano hydrophobic particles on the fiber surface and the control of particle size.

[0025] It has been verified that the quartz fiber cloth treated by the method of the present invention can fully interact with the resin matrix, effectively improving the interfacial bonding strength of the composite material. The mechanical properties of the nano-sizing agent reinforced quartz fiber cloth composite material obtained by the present invention are significantly improved compared with the reinforced composite material obtained by the traditional method. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a nano-sizing agent reinforced quartz fiber cloth composite material, comprising the following steps:

[0027] (1) dispersing a surfactant, a solvent and nano-hydrophobic particles by shearing to obtain a nano-sizing emulsion;

[0028] (2) under argon protection, the nano-sizing emulsion is deposited on the surface of the quartz fiber cloth by an aerosol deposition method, and the modified quartz fiber cloth is obtained after drying;

[0029] (3) mixing resin powder and inorganic powder to obtain mixed powder;

[0030] (4) Using the mixed powder as the resin matrix and the modified quartz fiber cloth as the reinforcement, a nano-sizing agent reinforced quartz fiber cloth composite material is obtained by hot pressing.

[0031] In the present invention, the aerosol deposition method is specifically:

[0032] The nano-sizing emulsion is subjected to spark ablation to obtain nano-aerosol, and the nano-aerosol is deposited on the surface of the quartz fiber cloth by carrier gas;

[0033] The flow rate of the carrier gas is 100 to 300 m / s, preferably 150 to 250 m / s, and more preferably 180 to 220 m / s.

[0034] In the present invention, the drying temperature is 110-130° C., preferably 120° C.; the drying time is 5-10 hours, preferably 8 hours.

[0035] In the present invention, the rotation speed of the shear dispersion is 1000-3000 rpm, preferably 1000-2000 rpm; the shear dispersion time is 10-30 min, preferably 20 min.

[0036] In the present invention, the surfactant comprises one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, polyoxyethylene alkylamine and polyoxyethylene alkylamide, preferably fatty alcohol polyoxyethylene ether; the solvent comprises one or more of N-methylpyrrolidone, methanol, ethanol, acetone, dioxane and tetrahydrofuran, preferably methanol.

[0037] In the present invention, the nano-hydrophobic particles include one or more of polyethylene nano-particles, sodium poly(ethylene acid) nano-particles, zinc oxide hydrophobic nano-particles, aluminum oxide hydrophobic nano-particles, super-hydrophobic PDMS nano-particles and nano-silicon dioxide, preferably polyethylene nano-particles and / or nano-silicon dioxide; the particle size of the nano-hydrophobic particles is 1 to 50 nm, preferably 1 to 30 nm, and more preferably 1 to 10 nm.

[0038] In the present invention, the mass ratio of the surfactant, the solvent and the nano hydrophobic particles is 20-30:20-30:15-35, preferably 22-28:22-28:18-32, and more preferably 24-26:23-25:20-30.

[0039] In the present invention, the resin powder comprises one or more of phenolic resin, cyanate resin and polyimide resin, preferably phenolic resin; the inorganic powder comprises one or more of talcum powder, calcium carbonate powder and wollastonite powder, preferably calcium carbonate powder; the mass ratio of the resin powder to the inorganic powder is 1:1 to 3, preferably 1:2.

[0040] In the present invention, the mass ratio of the reinforcement to the resin matrix is ​​1:1-1.5, preferably 1:1.5.

[0041] In the present invention, the temperature of the hot pressing molding is 300-400° C., preferably 320-380° C., and more preferably 350° C.; the pressure is 1-10 MPa, preferably 2-8 MPa, and more preferably 4-6 MPa.

[0042] The invention also provides a nano-sizing agent reinforced quartz fiber cloth composite material.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1

[0045] (1) 25 parts of alkylphenol polyoxyethylene ether were mixed with 28 parts of methanol, and then 30 parts of nano-silicon dioxide were added. After mixing, the mixture was put into a shear disperser and dispersed at 1000 rpm for 20 minutes to obtain a nano-sizing emulsion.

[0046] (2) Under argon protection, the nano-sizing emulsion was subjected to spark ablation (temperature above 1000°C) of an aerogel generator by an aerosol deposition method to form aerogel particles. The aerogel particles were filtered and deposited on the surface of quartz fiber cloth by a carrier gas to form nano-hydrophobic particles on the surface of the quartz fiber cloth. The cloth was dried at 120°C for 5 h to obtain a modified quartz fiber cloth. The flow rate of the carrier gas was 200 m / s.

[0047] (3) mixing phenolic resin powder and calcium carbonate powder in a mass ratio of 1:1 to obtain a mixed powder;

[0048] (4) Using modified quartz fiber cloth as reinforcement and mixed powder as resin matrix, the mixed powder is laid on each layer of modified quartz fiber cloth according to a mass ratio of 1:1.5, and a composite material is obtained by hot pressing at a temperature of 300°C and a pressure of 5 MPa.

[0049] Example 2

[0050] (1) 30 parts of fatty alcohol polyoxyethylene ether were mixed with 20 parts of dioxane, and then 25 parts of super-hydrophobic PDMS nanoparticles were added. After mixing, the mixture was put into a shear disperser and dispersed at 1000 rpm for 20 min to obtain a nano-sizing emulsion.

[0051] (2) Under argon protection, the nano-sizing emulsion was subjected to spark ablation (temperature above 1000°C) of an aerogel generator by an aerosol deposition method to form aerogel particles. The aerogel particles were filtered and deposited on the surface of quartz fiber cloth by a carrier gas to form nano-hydrophobic particles on the surface of the quartz fiber cloth. The cloth was dried at 120°C for 5 h to obtain a modified quartz fiber cloth. The flow rate of the carrier gas was 200 m / s.

[0052] (3) mixing cyanate resin powder and wollastonite powder in a mass ratio of 1:1 to obtain a mixed powder;

[0053] (4) Using modified quartz fiber cloth as reinforcement and mixed powder as resin matrix, the mixed powder is laid on each layer of modified quartz fiber cloth according to a mass ratio of 1:1.5, and a composite material is obtained by hot pressing at a temperature of 300°C and a pressure of 5 MPa.

[0054] Example 3

[0055] (1) 28 parts of polyoxyethylene alkylamine were mixed with 30 parts of acetone, and then 35 parts of sodium polyacrylate nanoparticles were added. After mixing, the mixture was put into a shear disperser and dispersed at 2000 rpm for 10 minutes to obtain a nano sizing emulsion.

[0056] (2) Under argon protection, the nano-sizing emulsion was subjected to spark ablation (temperature above 1000°C) of an aerogel generator by an aerosol deposition method to form aerogel particles. The aerogel particles were filtered and deposited on the surface of quartz fiber cloth by a carrier gas to form nano-hydrophobic particles on the surface of the quartz fiber cloth. The cloth was dried at 120°C for 5 h to obtain a modified quartz fiber cloth. The flow rate of the carrier gas was 200 m / s.

[0057] (3) mixing polyimide resin powder and talc powder in a mass ratio of 1:1 to obtain a mixed powder;

[0058] (4) Using modified quartz fiber cloth as reinforcement and mixed powder as resin matrix, the mixed powder is laid on each layer of modified quartz fiber cloth according to a mass ratio of 1:1.5, and a composite material is obtained by hot pressing at a temperature of 300°C and a pressure of 5 MPa.

[0059] Example 4

[0060] (1) 30 parts of polyoxyethylene alkylamide were mixed with 25 parts of tetrahydrofuran, and then 29 parts of super-hydrophobic PDMS nanoparticles were added. After mixing, the mixture was put into a shear disperser and dispersed at 2000 rpm for 10 min to obtain a nano-sizing emulsion.

[0061] (2) Under argon protection, the nano-sizing emulsion was subjected to spark ablation (temperature above 1000°C) of an aerogel generator by an aerosol deposition method to form aerogel particles. The aerogel particles were filtered and deposited on the surface of quartz fiber cloth by a carrier gas to form nano-hydrophobic particles on the surface of the quartz fiber cloth. The cloth was dried at 120°C for 5 h to obtain a modified quartz fiber cloth. The flow rate of the carrier gas was 30 m / s.

[0062] (3) mixing phenolic resin powder and calcium carbonate powder in a mass ratio of 1:1 to obtain a mixed powder;

[0063] (4) Using modified quartz fiber cloth as reinforcement and mixed powder as resin matrix, the mixed powder is laid on each layer of modified quartz fiber cloth in a mass ratio of 1:1, and a composite material is obtained by hot pressing at a temperature of 300°C and a pressure of 5 MPa.

[0064] Example 5

[0065] (1) 20 parts of fatty alcohol polyoxyethylene ether were mixed with 30 parts of N-methylpyrrolidone, and then 30 parts of alumina hydrophobic nanoparticles were added. After mixing, the mixture was put into a shear disperser and dispersed at 2000 rpm for 10 min to obtain a nano sizing emulsion.

[0066] (2) Under argon protection, the nano-sizing emulsion was subjected to spark ablation (temperature above 1000°C) of an aerogel generator by an aerosol deposition method to form aerogel particles. The aerogel particles were filtered and deposited on the surface of quartz fiber cloth by a carrier gas to form nano-hydrophobic particles on the surface of the quartz fiber cloth. The cloth was dried at 120°C for 5 h to obtain a modified quartz fiber cloth. The flow rate of the carrier gas was 30 m / s.

[0067] (3) mixing phenolic resin powder and calcium carbonate powder in a mass ratio of 1:1 to obtain a mixed powder;

[0068] (4) Using modified quartz fiber cloth as reinforcement and mixed powder as resin matrix, the mixed powder is laid on each layer of modified quartz fiber cloth in a mass ratio of 1:1, and a composite material is obtained by hot pressing at a temperature of 300°C and a pressure of 5 MPa.

[0069] Comparative Example 1

[0070] The quartz fiber was immersed in a 5% ethanol solution of phenolic resin and irradiated with a gamma ray Co source at a rate of 4.8 kGy / h and a irradiation dose of 200 kGy. The fiber was taken out and dried to obtain the modified quartz fiber. The modified quartz fiber and phenolic resin were pressed into a composite material by hot pressing at 300°C and 5 MPa.

[0071] Comparative Example 2

[0072] The same as Example 1, except that the quartz fiber cloth is immersed in the nano-sizing emulsion, immersed for 30 minutes with the assistance of ultrasound, taken out and dried at 120° C. for 9 hours to obtain the modified quartz fiber cloth.

[0073] Comparative Example 3

[0074] (1) 35 g of styrene-maleic anhydride copolymer powder (number average molecular weight of 6000, acid value of 345 mgKOH / g), 1050 g of distilled water, and 21 g of potassium hydroxide were added to a reaction vessel equipped with a condensation reflux device and a stirring paddle, and the mixture was rapidly stirred at 80° C. until the solution became transparent, thereby obtaining a styrene-maleic anhydride saponified solution.

[0075] (2) 194 g of a phenoxy resin solution (the weight average molecular weight of the phenoxy resin is 30,000 and the mass fraction of the phenoxy resin is 32%) obtained by dissolving in xylene and 3 g of polyethylene glycol monolaurate are uniformly mixed in a reaction container, and styrene-maleic anhydride saponified solution is gradually added under continuous stirring at a speed of 10,000 r / min for emulsification. After the emulsification is completed, the organic solvent is removed by rotary evaporation to obtain an emulsion, which is a sizing agent.

[0076] (3) The sizing agent is diluted with water to 1.0% and attached to the quartz fiber cloth by an impregnation method, and then dried at 130° C. A composite material is prepared by hot pressing the phenolic resin as a matrix material and the sized quartz fiber cloth at 300° C. and 5 MPa.

[0077] Experimental Example 1

[0078] The hydrophobicity test of the modified quartz fiber cloth obtained in Examples 1 to 5 was performed, and the results are shown in Table 1 below.

[0079] Table 1 Hydrophobicity test of modified quartz fiber cloth

[0080] project Contact angle with water drop (°) Roll angle (°) Example 1 161.5 5 Example 2 162 4 Example 3 159.5 5 Example 4 160.5 5 Example 5 158.4 6

[0081] Experimental Example 2

[0082] The composite materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to shear and bending strength tests, and the modified quartz fiber cloth was subjected to a tensile strength test. The results are shown in Table 2 below.

[0083] Table 2 Performance test results

[0084]

[0085] From the above examples, it can be seen that the present invention provides a nano-sizing agent-reinforced quartz fiber cloth composite material and a preparation method thereof. As can be seen from Table 1, the hydrophobic properties of the modified quartz fiber cloth obtained by depositing the sizing agent on the surface of the quartz fiber by the aerosol deposition method of the present invention for surface hydrophobic modification are significantly improved;

[0086] As can be seen from Table 2, the interfacial bonding force of quartz fiber and resin matrix in the composite material prepared by traditional several methods is poorer than the composite material of the present application. The present invention, by adding nano hydrophobic particles, firmly attaches the sizing emulsion to the surface of quartz fiber cloth by aerosol deposition, not only improves the surface hydrophobicity of quartz fiber, but also improves its interfacial bonding force with resin matrix, and finds by tensile strength test, more significantly improves the flexibility of composite material, compared to the quartz fiber processed by traditional method, the tensile strength of quartz fiber obtained by the processing method of the present invention is reduced, because tensile strength and impact strength are inversely proportional, the larger the tensile strength, the harder and more brittle the material is, and its impact strength will be worse, and the material of the modified quartz fiber cloth obtained by the present invention is more flexible, not easy to break during stretching, and has good mechanical properties.

[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a nano-sizing agent reinforced quartz fiber cloth composite material, characterized in that: The following steps are involved: (1) dispersing a surfactant, a solvent and nano-hydrophobic particles by shearing to obtain a nano-sizing emulsion; (2) under argon protection, the nano-sizing emulsion is deposited on the surface of the quartz fiber cloth by an aerosol deposition method, and the modified quartz fiber cloth is obtained after drying; (3) mixing resin powder and inorganic powder to obtain mixed powder; (4) Using the mixed powder as the resin matrix and the modified quartz fiber cloth as the reinforcement, a nano-sizing agent reinforced quartz fiber cloth composite material is obtained by hot pressing.

2. The preparation method according to claim 1, characterized in that: The aerosol deposition method is specifically: The nano-sizing emulsion is subjected to spark ablation to obtain nano-aerosol, and the nano-aerosol is deposited on the surface of the quartz fiber cloth by carrier gas; The flow rate of the carrier gas is 100-300 m / s.

3. The preparation method according to claim 1 or 2, characterized in that: The surfactant comprises one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, polyoxyethylene alkylamine and polyoxyethylene alkylamide; the solvent comprises one or more of N-methylpyrrolidone, methanol, ethanol, acetone, dioxane and tetrahydrofuran.

4. The preparation method according to claim 3, characterized in that: The nano hydrophobic particles include one or more of polyethylene nano particles, sodium polyvinyl acid nano particles, zinc oxide hydrophobic nano particles, aluminum oxide hydrophobic nano particles, super hydrophobic PDMS nano particles and nano silicon dioxide, and the particle size of the nano hydrophobic particles is 100-200nm.

5. The preparation method according to claim 1, 2 or 4, characterized in that: The mass ratio of the surfactant, the solvent and the nano hydrophobic particles is 20-30:20-30:15-35.

6. The preparation method according to claim 5, characterized in that: The resin powder comprises one or more of phenolic resin, cyanate resin and polyimide resin; the inorganic powder comprises one or more of talc powder, calcium carbonate powder and wollastonite powder; the mass ratio of the resin powder to the inorganic powder is 1:1-3.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the reinforcement to the resin matrix is ​​1:1 to 1.

5.

8. The preparation method according to claim 1, 6 or 7, characterized in that: The temperature of the hot pressing molding is 300-400° C., and the pressure is 1-10 MPa.

9. The nano-sizing agent reinforced quartz fiber cloth composite material prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Cited By

  • Nano sizing agent reinforced quartz fiber cloth composite material and preparation method thereof

    CN121716333A